The Demographic Transformation of America - Olshansky, S. Jay (Daedalus, 2015)
The face of aging in America is about to change. Within the next thirty years, the U.S. population will experience a permanent change in its age structure, and there is reason to believe that cohorts reaching older ages in the future will be far different from those reaching older ages today. In this essay, I explain why life expectancy in the United States is likely to diverge from that experienced by the rest of the developed world; describe recent trends in healthy life expectancy; and examine how the age structure of the United States will by mid-century be different from that found today.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDAzMjY